Children’s practices and engagement in e-Reading for pleasure: A case study of a Malaysian Primary School / Seyedeh Ghazal Ghalebandi - Seyedeh Ghazal , Ghalebandi (2020)
Children nowadays have been exposed to on-screen reading or e-reading since the development of mobile application and devices to support reading and learning activities. The reading for pleasure declines as children grow older. Studies highlighted the reduces children’s time and motivation for voluntary reading because of competing interests and other leisure activities. It is believed that recent technological advancements are also contributing to the decline in reading for pleasure. This study employed a case study approach to understanding children’s practices and engagement in e-reading for pleasure context. The following research questions were put forward in the investigation: a) how do children demonstrate their e-reading experience when using touch screen device? b) What drives children emotional engagement in e-reading exercise when using touch screen device? c) What drives children behavioral engagement in e-reading exercise when using touch screen device? d) How do children demonstrate their understanding of the e-reading exercise when using touch screen device? The study was conducted based on the engagement model of reading development as the theoretical underpinning to guide the study as well as selfdetermination theory. Engagement model includes three engagement components namely emotional, behavioral, and cognitive, and self-determination theory comprises autonomy, competence, and relatedness. Participants in the study include ten multilingual children aged between seven to eight years old from a primary school and their parents. The study adopted observation and interview as data collection techniques. Data collections were conducted at the library and computer room inside the school compound where the children were given iPad that was installed with several reading applications for e-reading sessions. Each e-reading session took around 10 to 15 minutes, a total of eight reading activities were conducted in individual and shared settings. Thematic analysis was used as an inductive analysis through coding strategies to generate relevant themes or concepts from the data. The findings from the study reveal that children exhibited passive and active reading behaviors in individual and shared settings. They experienced enthusiasm and enjoyment as well as boredom to complete or continue the reading activities through their interaction with interface and peer interaction. Several motivation and engagement constructs are discovered to influence the emergent themes from the data. Children demonstrated RECEIVE construct through attentiveness and taking an interest in the genre, topics, and context of reading apps as well as RESPONSE through the excitement and amusement towards interaction with the interface and peer interaction. The PHYSICAL EFFORT revolved around applying sensory skills and touched-based gestures to operate the device or get lost in their favorite topic to read such as navigating the app interface and manipulating the screen. The MENTAL EFFORT corresponded with commenting about the app and the content, asking questions, and showing more interest in visual and audition features of reading apps. Moreover, it was evident that children's PERCEIVED VALUE of reading was influenced by verbal information they receive from parents or guardians highlighting the importance of reading and learning in English. Thus, not only the reading from the iPad itself was enjoyable, but also valuable and supported. In addition, SELF-EFFICACY was regarded to their ability to interact with iPad and read in English; as reported by parents on children’ home literacy practices SCAFFOLDING. Children used several cognitive strategies to engage with text such as GUESSING the meaning of unfamiliar words, making ASSOCIATIONS between visual and verbal information, providing SYNONYMS, and SUMMARIZING the key events in proper sequences. However, the design of reading apps made it difficult for children to fully understand the text and recall the key events in the correct sequence. It maintains that assisted cognitive tools should be embedded for the scaffolding and supporting children's information retrieval process. No empirical study could be located in the form of case study to explore children’s e-reading experiences and engagement when the intention is reading for pleasure using storybooks and educational apps in the second language, particularly for those who are in the stage of learning to read (grade 1 and 2). Children’s reading motivation and engagement will encourage a satisfactory experience, improved reading performance (comprehension), and persistent in reading habits.